2020
DOI: 10.7454/jessd.v3i2.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leaching on the Reclamation of Saline Soils as Affected by Different Organic and Inorganic Amendments

Abstract: Soil salinity, which poses one of the greatest threats to sustainable crop production worldwide, can be ameliorated through various approaches, such as leaching, mulching, and amendment application. The effects of leaching and amendments on saline soil reclamation have been studied separately, but their interaction is poorly elucidated. Therefore, a column experiment was designed with soils that were subjected to leaching with 2 and 4 pore volume (PV) of water and compared with non-leached soils (NLS) to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…SRDI (2010) also stated that Na + , Ca 2+ , Mg 2+ and K + are the dominant cations found in saline soils, and the ionic preponderance decreased in the order of Na + > Mg 2+ > Ca 2+ > K + in areas under the influence of brackish water. The positive correlation of EC with that of other cations and anions (Table 1 and 2) in the present study was in consistent with other findings (Cebas-Csic et al, 1997;Roy et al, 2020;Roy and Chowdhury, 2020b). The EC of soil solution is the measure of its ability to conduct an electric current which usually depends on the number of ions present in the soil, and the higher the concentration of dissolved ions in soil solution, the higher its EC (Brady and Weil, 2005).…”
Section: Map Visualizationssupporting
confidence: 92%
See 2 more Smart Citations
“…SRDI (2010) also stated that Na + , Ca 2+ , Mg 2+ and K + are the dominant cations found in saline soils, and the ionic preponderance decreased in the order of Na + > Mg 2+ > Ca 2+ > K + in areas under the influence of brackish water. The positive correlation of EC with that of other cations and anions (Table 1 and 2) in the present study was in consistent with other findings (Cebas-Csic et al, 1997;Roy et al, 2020;Roy and Chowdhury, 2020b). The EC of soil solution is the measure of its ability to conduct an electric current which usually depends on the number of ions present in the soil, and the higher the concentration of dissolved ions in soil solution, the higher its EC (Brady and Weil, 2005).…”
Section: Map Visualizationssupporting
confidence: 92%
“…Compared to the pre-monsoon season, the soil pH of all the sampling sites in the post-monsoon season increased which was likely due to the removal of SO 4 2with rain water during the monsoon period. In the recent study, Roy and Chowdhury (2020b) observed that the leaching of acidic saline soils resulted in an increased pH compared to non-leached soils.…”
Section: Map Visualizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study case, saline soils should be treated, and subsequently sodic soils, in order to reduce the concentration of salts to the appropriate degree for the growth of plant roots and even the appropriate depth for the roots [114][115][116][117][118][119][120].…”
Section: Discussionmentioning
confidence: 99%
“…Cotton and sugar beet are the most important salt-tolerant crops, while sugar cane, fava beans, and peas are the least tolerant of salinity. Most vegetable crops are moderately resistant to salinity, while most fruit crops, especially deciduous, are sensitive to salinity [114][115][116][117][118][119][120][121][122][123][124].…”
Section: Discussionmentioning
confidence: 99%